Nasopharyngeal bacterial load as a marker for rapid and easy diagnosis of invasive pneumococcal disease in children from Mozambique. - Pedro Brotons; Quique Bassat; Miguel Lanaspa; Desiree Henares; Amaresh Perez-Arguello; Lola Madrid; Reyes Balcells; Sozinho Acacio; Maria Andres-Franch; Maria Angeles Marcos; Ana Valero-Rello; Carmen Muñoz-Almagro (PLoS ONE)
Background Current diagnostic methods for detection of Streptococcus pneumoniae in children with suspected invasive pneumococcal disease have limitations of accuracy, timeliness, and patient convenience. This study aimed to determine the performance of pneumococcal load quantified with a real-time polymerase-chain reaction in nasopharyngeal samples to diagnose invasive pneumococcal disease in children. Methods Matched case-control study of patients <5 years of age with invasive pneumococcal disease admitted to the Manhiça District Hospital (Mozambique) and asymptomatic controls recruited in different periods between 2006 and 2014. Cases were confirmed by a positive bacterial culture for S. pneumoniae in blood or cerebrospinal fluid. Nasopharyngeal aspirates were collected from cases and controls and pneumococcal density was quantified by lytA real-time polymerase-chain reaction. Results Thirty cases (median age 12.8 months) and sixty controls (median age 11.7 months) were enrolled and 70% of them were male. Nasopharyngeal pneumococcal carriage was high in both groups: 28/30 (93.3%) for cases vs. 53/60 (88.3%) for controls (p = 0.71). Mean nasopharyngeal pneumococcal load was identified as a marker for invasive pneumococcal disease (7.0 log10 copies/mL in cases vs. 5.8 log10 copies/mL in controls, p<0.001) and showed good discriminatory power (AUC-ROC: 82.1%, 95% CI 72.5%-91.8%). A colonization density of 6.5 log10 copies/mL was determined as the optimal cut-off value to distinguish cases from controls (sensitivity 75.0%, specificity 73.6%). Conclusion Use of non-invasive nasopharyngeal aspirates coupled with rapid and accurate quantification of pneumococcal load by real-time polymerase chain reaction has the potential to become a useful surrogate marker for early diagnosis of invasive pneumococcal disease in children.